Height Estimation of Target Objects Based on Structured Light. (1st November 2018) - Liu, Wei; Zhao, Yongsheng
Abstract : The height estimation of the target object is an important research direction in the field of computer vision. The three-dimensional reconstruction of structured light has the characteristics of high precision, noncontact, and simple structure and is widely used in military simulation and cultural heritage protection. In this paper, the height of the target object is estimated by using the word structure light. According to the height dictionary, the height under the offset is estimated by the movement of the structured light to the object. In addition, by effectively preprocessing the captured structured light images, such as expansion, seeking skeleton, and other operations, the flexibility of estimating the height of different objects by structured light is increased, and the height of the target object can be estimated more accurately.